APPLICATION OF P CHART AND CUSUM CHART TO EVALUATE INCREASING COVID-19 CASES IN DKI JAKARTA PROVINCE - Muhammad Rinaldi Saputra, Andi
Covid-19's rapid spread in Jakarta is a serious concern for the DKI Jakarta Provincial Government. Various government policies, such as large-scale social controls (PSBB) and the Implementation of Restrictions on Group Events (PPKM) have been introduced to slow the spread of Covid-19. In order to expedite the handling of Covid-19, this regulation controls restrictions on activities such as social and cultural activities, schooling, religion, modes of transportation, and other activities. Statistical instruments, such as control charts, may be used to determine if the spreading of Covid-19 is under control or not. The value of the proportion of positive cases Covid-19 using P Chart and CUSUM Chart will be observed using data from the test specimen Covid-19 in Jakarta. Furthermore, the shift in the value of the proportion as the number of cases increases will be noticeable. The spreading of Covid-19 has not been statistically controlled so far, according to the control chart obtained. Several findings indicate an upward trend, suggesting that the proportion of positive cases Covid-19 is rising. Of course, the public's conduct in Jakarta has served as a model for the government in designing policies to tackle the spread of Covid-19. However, due to the high mobility of Jakarta residents and a lack of consistency in the region, Covid-19 has spread out of control. A policy evaluation of the effectiveness of handling the virus's spread should be conducted at some point in the future, so that positive Covid-19 cases do not continue to rise every day, especially in DKI Jakarta Province.